# Power to Characteristic Power of Field is Monomorphism

## Contents

## Theorem

Let $F$ be a field whose characteristic is $p$ where $p \ne 0$.

Let $n \in \Z_{\ge 0}$ be any positive integer.

Let $\phi_n: F \to F$ be the mapping on $F$ defined as:

- $\forall x \in F: \phi_n \left({x}\right) = x^{p^n}$

Then $\phi_n$ is a (field) monomorphism.

## Proof

Proof by induction:

For all $n \in \Z_{\ge 0}$, let $P \left({n}\right)$ be the proposition:

- $\phi_n$ is a (field) monomorphism.

$P(0)$ is trivially true:

- $\phi_0 \left({x}\right) = x^{p^0} = x^1 = x$

... and we see that $\phi_0$ is the identity automorphism.

This is not the zero homomorphism.

So from Ring Homomorphism from Field is Monomorphism or Zero Homomorphism, it follows that $\phi_0$ is a ring monomorphism.

### Basis for the Induction

First we need to show that $P(1)$ is true:

- $\phi_1 \left({x}\right) = x^{p^1} = x^p$ is a (field) monomorphism.

This is demonstrated to be a monomorphism in Power to Characteristic of Field is Monomorphism.

### Induction Hypothesis

Now we need to show that, if $P \left({k}\right)$ is true, where $k \ge 1$, then it logically follows that $P \left({k+1}\right)$ is true.

So this is our induction hypothesis:

- $\phi_k \left({x}\right) = x^{p^k}$ is a (field) monomorphism.

Then we need to show:

- $\phi_{k+1} \left({x}\right) = x^{p^{k+1}}$ is a (field) monomorphism.

### Induction Step

This is our induction step:

\(\displaystyle \phi_{k+1} \left({a + b}\right)\) | \(=\) | \(\displaystyle \left({a + b}\right)^{p^{k+1} }\) | |||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle \left({\left({a + b}\right)^{p^k} }\right)^p\) | |||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle \left({a^{p^k} + b^{p^k} }\right)^p\) | Induction Hypothesis | ||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle \left({a^{p^k} }\right)^p + \left({b^{p^k} }\right)^p\) | Basis for the Induction | ||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle a^{p^{k+1} } + b^{p^{k+1} }\) | |||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle \phi_{k+1} \left({a}\right) + \phi_{k+1} \left({b}\right)\) |

Multiplication is more straightforward:

\(\displaystyle \phi_{k+1} \left({a b}\right)\) | \(=\) | \(\displaystyle \left({a b}\right)^{p^{k+1} }\) | |||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle a^{p^{k+1} } b^{p^{k+1} }\) | |||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle \phi_{k+1} \left({a}\right) \phi_{k+1} \left({b}\right)\) |

... and does not rely on the induction process.

Thus, $\phi_{k+1}$ is a homomorphism.

$\phi_{k+1}$ is not the zero homomorphism, since $\phi_{k+1} \left(1\right) = 1^{p^{k+1} } = 1 \ne 0$.

So from Ring Homomorphism from Field is Monomorphism or Zero Homomorphism, it follows that $\phi_{k+1}$ is a ring monomorphism.

So $P \left({k}\right) \implies P \left({k+1}\right)$ and the result follows by the Principle of Mathematical Induction.

Therefore:

- $\forall n \in \Z_{\ge 0}: \phi_n$ is a (field) monomorphism.

$\blacksquare$

## Also see

- Prime Power of Sum Modulo Prime, where the same technique is used.

## Sources

- 1964: Iain T. Adamson:
*Introduction to Field Theory*... (previous) ... (next): $\S 1.3$: Theorem $3.3$ Corollary